Four-quadrant switch-mode gyrator - Dinçbakır, Cenk; Bilgiç, Mehmet Oruç (IEEE, 2008)
A gyrator design based on an inductor coupled double bridge converter is presented. It is shown that this gyrator can operate in four-quadrant mode by using bi-directional MOS switches without the necessity of any feedback control circuit. There are different usage areas of such a gyrator. Some of which can be used for conversions of voltage to current, current to voltage, capacitor to inductor and Resistance to Resistance. In this paper, the dynamic and static gyrator behavior is first simulated and some of above conversions are also tested.
Keywords: Gyrators; Inductors; Voltage; Coupling circuits; Bridge circuits; Bidirectional control; Switching circuits; Switches; Feedback control; Feedback circuits